Phytochemical Analysis and Anti-Inflammatory Activity of the Extracts of the African Medicinal Plant Ximenia caffra - Jing Zhen; Yue Guo; Tom Villani; Steve Carr; Thomas Brendler; Davis R. Mumbengegwi; Ah-Ng Tony Kong; James E. Simon; Qingli Wu (Journal of Analytical Methods in Chemistry)
A method was developed for identification and quantification of polyphenols in the leaves of Ximenia caffra using HPLC/UV/MS. Based on analyzing the MS and UV data and in comparison to the authentic standards, a total of 10 polyphenols were identified and quantified, including gallic acid, catechin, quercetin, kaempferol, and their derivatives. The total content of these compounds was found to be approximately 19.45 mg/g in the leaf and the most abundant is quercetin-rutinoside (9.08 mg/g). The total phenolic content as measured by Folin-Ciocalteu assay was 261.87 ± 7.11 mg GAE/g and the total antioxidant capacity as measured in vitro was 1.46 ± 0.01 mmol Trolox/g. The antiproliferative effect of the leaf extract was measured by MTS assay with IC50 value of 239.0 ± 44.5 μg/mL. Cell-based assays show that the leaf extract inhibits the mRNA expression of proinflammatory genes (IL-6, iNOS, and TNF-α) by using RT-qPCR, implying its anti-inflammatory effects. It was further demonstrated that the underlying therapeutic mechanism involves the suppression of NF-κB, a shared pathway between cell death and inflammation.